The Rambles of a Rat - A. L. O. E., 1821-1893 (Salt Lake City, UT : Project Gutenberg, 2009)
"The Rambles of a Rat" by A. L. O. E. is a fictional narrative written in the mid-19th century. The story tells of the adventures of a black rat named Ratto and his experiences alongside other rats and their encounters with humans, offering an amusing yet insightful look at the lives of these often-misunderstood creatures. The book plays with anthropomorphism, showcasing the character's thoughts and emotions while reflecting on social issues and the nature of humanity. The opening of the book introduces Ratto, the main character, and his family of rats living in a shed near London. Ratto recalls the joyous and carefree days spent with his brothers, particularly focusing on the piebald brother named Oddity. As they explore their environment, Ratto's brothers fall victim to a trap while pursuing a tempting feast, leading to discussions about the nature of man and the dangers rats face. Amidst these adventures, Ratto meets two abandoned human boys, Bob and Billy, which allows for poignant reflections on poverty and companionship, showcasing the contrast between the lives of rats and humans. (This is an automatically generated summary.)
Release date is 2009-08-30
E-text prepared by Louise Hope
Keywords: Rats -- Juvenile fiction